O direito aplicável às decisões produzidas por software e machine learning: a influência e aplicação do direito brasileiro à robótica e inteligência artificial - Higasi, Plínio Kentaro de Britto Costa (2021)
The present work will raise information and research already carried out by several authors in the Law sectors, which demonstrate the impact on legal issues after the growth in the use of machine learning, which will produce results for society based on the automation of decision-making, according to the parameters- base entered by the software programmer, and the consequences until reaching the ideal parameter. With the frequent research and achievements related to the evolution of Artificial Intelligence, it is evident that its growth will generate more legal facts, that is, facts that matter to the Law and generate incidence of legal norms. This work does not seek to train automation based on machine learning, but only to seek work and reflections on what this will bring to Brazilian law, as some authors explains, and the results were obtained from the jurisprudential and doctrinal analysis of the law applicable to technology, and the conclusion reached is that the responsibility can be attributed to those who produced the technology in question, whether in terms of software or hardware, considering the peculiarities analyzed in an eventual lawsuit